Angiogenesis in cancer - Prager, G. W.; Poettler, M. (Hämostaseologie, 2012)
Etiological concepts on cancer development, malignant growth and tumour propagation have undergone a revolutionary development during recent years: Among other aspects, the discovery of angiogenesis – the growth of new blood vessels from pre-existing vasculature – as a key element in the pathogenesis of malignancy has opened an abundance of biologic insights and subsequent therapeutic options, which have led to improved prognosis in many cancers including those originating from colon, lung, breast and kidney. Thereby, targeting the major pro-angiogenic stimulus vascular endothelial growth factor (VEGF) became the focus for therapeutic interventions. However, the use of VEGF-targeting drugs has been shown to be of limited efficacy, which might lie in the fact that tumor angiogenesis is mediated by a variety of different subcellular systems.This review focuses on the basic mechanisms involved in angiogenesis, which potentially represent novel targets for pharmacological agents in the treatment of malignancies.
Keywords: Angiogenesis; cancer; endothelial cells